Stres, Pola Konsumsi, dan Pola Istirahat Mahasiswa Tingkat Akhir Fakultas Kesehatan Masyarakat Universitas Nusa Cendana - Abel, Yurike; Nur, Marselinus Laga; Toy, Sarci Magdalena; Jutomo, Lewi (Timorese Journal of Public Health, 2019)
The length of time required by students to do a thesis can be a stressor for last term students. The aim of this study was to determine the effect of stress on consumption patterns and rest patterns in last term students of the Faculty of Public Health, Nusa Cendana University. The study was observational analytic and used the cross-sectional study design. The sample size of 71 people was selected using a simple random sampling technique. The statistical test used was a simple linear regression with α = 0.05. The results showed that most respondents experienced severe stress (73.23%), and had poor consumption patterns and resting patterns (69.01% and 63.38%). The statistical test results showed that stress affected consumption patterns (p = 0.03) and rest patterns (p = 0.039) in last term students of FKM Undana.